Management of post-operative complication of tonsillectomy - Nasb Nhab, Shakir (International Journal of Psychosocial Rehabilitation, 2022)
Tonsillitis is the inflammation of the tonsils (two oval-shaped pads of tissue at the back of the throat one tonsil on each side) due to infection. It is mostly caused by viral or bacterial infection. When caused by a bacterium belonging to the Group AStreptococcus. Tonsillectomy is performed under general anaesthesia and can commonly be performed as a day case procedure both in adults and children. Cold steel dissection is the most commonly performed surgical technique, where extracapsular dissection is performed to remove the tonsil from the underlying muscles. Any subsequent bleeding is controlled by ties and/or bipolar diathermy. Surgery leaves exposed pharyngeal muscle within the tonsillar fossa which is allowed to heal by secondary intention over a period of 5-10 days.